Restricted opportunity: the missing point in Nepali migration- discourse - Karki, Pralhad; Manandhar, K D (Journal of Advanced Academic Research, 2017)
Restricted opportunity is the key push-factor that compels Nepalis to leave home for job abroad. Yet it is not taken seriously in the Nepali migration-discourse. A general survey of literature of migration issues in Nepal reveals how the factor is sidelined by stakeholders of migration particularly policy makers and those who are responsible for managing the foreign employment sector. Scholars are mostly found not emphasizing the point in their academic rhetoric on migration issues. Because of this there is a trend to surround migration discussion with two themes - remittance and labor-export.  Although the themes are important and relevant, they alone cannot make the migration discourse complete. Due attention should therefore be given to the restricted opportunity and all components attached to it.  Journal of Advanced Academic Research, Vol. 3, No. 2, 2016 150-159